Metamodernism the future of theory - Josephson-Storm, Jason Ānanda (The University of Chicago Press, 2021)
For decades, scholars have been calling into question the universality of disciplinary objects and categories. The coherence of defined autonomous categories--such as religion, science, and art--has collapsed under the weight of postmodern critiques, calling into question the possibility of progress and even the value of knowledge. Jason